Topography Of Greater Palatine Foramen In Relation to Interpalatine Suture in Adult Dry Skull - Joel Simon, Christopher; Saravanan,; Duraisawamy, Revathy; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Introduction The greater palatine foramens (GPF) are close to the palate's lateral border, behind the palatomaxillary suture, which previously were deep vascular grooves. The greater palatine foramen (GPF) is related to the upper 3rd molar tooth in most of the skulls (55%), the 2nd molar in (12%), between the 2nd & 3rd molar in (19%), and retromolar in (14%). The shape of the foramen is elongated antero-posteriorly; however, an unusually crescent-shaped foramen is rare. At either posterior angle of the hard palate is the greater palatine foramen, for the transmission of the descending palatine vessels and greater palatine nerve; and running anteriorly (forward) and medially (towards the center-line) from it is a groove, for the same vessels and nerve. To anesthetize the posterior part of the soft palate for various surgical procedures, knowledge of the position of the greater palatine foramen (GPF) is very important. Blocking of the maxillary division of the trigeminal nerve or its branches for local anesthesia is common practice for maxillofacial surgeries. Aim To analyze the relationship of the greater palatine foramen to the interpalatine suture in an adult dry skull. Material and Method The measurements between the reference points were done using the following instruments: a divider and a ruler. The first measurements were performed from the right and left greater palatine foramens to the interpalatine suture. One point of the divider is placed on the greater palatine foramen, and the other point is placed on the interpalatine suture, and the distance between them is measured with the help of a ruler. Totally 100 skulls were measured with the same procedure. Result Totally 100 skulls were measured, and the total mean value is 16.4 and the standard deviation is 4.96. The minimum value of the right greater palatine foramen to the interpalatine suture is 1.30, and the maximum is 2.0, and the minimum value of the left greater palatine foramen to the interpalatine suture is 1.40, and the maximum is 2.0. The mean value for the minimum and maximum of the right greater palatine foramen to the interpalatine suture is 1.65, and the standard deviation is 1.41. The mean value for the minimum and maximum of the left greater foramen to the interpalatine to interpalatine suture is 1.70, and the standard deviation is 1.46.